Effects of warming and nitrogen addition on nutrient resorption efficiency in an alpine meadow on the northern Tibetan Plateau. Issue 4 (4th July 2018) - Zong, Ning; Shi, Peili; Chai, Xi
ABSTRACT: The increase in two controversial global environmental issues, climate warming and nitrogen (N) deposition, may have distinct effects on the processes and functioning of terrestrial ecosystems. Nutrient resorption is an important determinant of plant community nutrient dynamics, especially in nutrient-limited ecosystems, but information about N and phosphorus (P) resorption in alpine ecosystems is still lacking. A long-term simulated warming and exogenous N addition experiment initiated in July 2010 was conducted in an alpine meadow in Damxung County in northern Tibet. The experiment consisted of conditions of warming and no warming crossed with three N addition levels: 0 (CK), 20 (N20), and 40 (N40) kg N · ha −1 · year −1 . With increasing N addition levels, the N content and the N/P ratio in plant leaves gradually increased, while the P limitation of plant growth was aggravated by N addition. The moderate N addition level (N20) increased plant N resorption efficiency (NRE), while the high N addition level (N40) had no effect on the NRE of Kobresia pygmaea or Anaphalis xylorhiza . N addition significantly increased the P resorption efficiency (PRE) in Stipa capillacea leaves. However, N addition did not change the community NRE or the community PRE. The soil N content decreased under the warming treatment. At the community level, warming significantly increased the NRE by 12% and 16%, and the PRE by 26% and 24% under the CK and N40 treatments, respectively. The NRE and PRE were higher in S. capillacea than in K. pygmaea and A. xylorhiza, especially at the high N addition level (38% and 45% higher NRE and 36% and 15% higher PRE compared to K. pygmaea and A. xylorhiza, respectively). Correlation analysis showed that the NRE and PRE in plant leaves were mainly mediated by soil inorganic N availability, and tended to decrease with increase of soil N availability, suggesting that N loss due to warming could induce changes in nutrient resorption in alpine ecosystems. The species-specific responses to N addition and the stronger competitive advantage of S. capillacea may change the community structure and subsequently affect the decomposition process in this alpine meadow under future global climate change scenarios.